Reproductive pattern and gonad maturation of sea cucumber, Holothuria scabra in sea pens and tank - Nor Anggeriani Arsad (2018)
The valuable sea cucumber, Holothuria scabra is one of the species that can produce a high grade of beche-de-mer. Overexploitation and overfishing led to depletion of this species in wild. To overcome the issue of the depletion, it is necessary to figure out the reproductive pattern and factors that can regulate the reproduction system of H. scabra in sea pens as well as in tank.Therefore, a study was conducted with aims; (1) to determine the reproductive pattern of H. scabra and timing of gamete availability in Kudat and Kunak, Sabah (2) to determine the correlation between the reproductive patterns with the environmental parameters and (3) to compare the broodstock growth and reproductive performance in sea pens and tank. Reproductive pattern of H. scabra in Limau-Limauan Kudat (N06°49’24.4”, E116°51’42.0”) and Telaga Tujuh Kunak (N04°39’52.05”, E118°15’49.01”) in Sabah were studied from July 2015 until August 2016. The environmental parameters were recorded monthly. In total, 210 of H. scabra were collected in Kudat and 159 in Kunak. The gonad index (GI) was calculated and histological examination was performed to determine the gonad maturity of H. scabra. In Kudat, the reproductive pattern occurred annually, begin in July 2015 and lasted until November 2015. Whereas in Kunak, no obvious season noticed but the GI was extremely high in September 2015. The reproductive pattern of H. scabra in Kudat and Kunak did not show any significant (p>0.05) relationship with any environmental parameters (temperature, salinity, chlorophyll a, organic matter and precipitation). Study on growth and reproductive performance of broodstock in sea pens (Limau-Limauan Kudat, N06°49’24.4”, E116°51’42.0” and Ambong Kota Belud, N06°18’23.0”, E116°19’44.0”) and tank (set in the UMS hatchery) was conducted from October 2016 until February 2017. Ninety individuals of H. scabra were collected from Limau-Limauan, Kudat and divided equally to Kudat, Ambong and tank. The environmental parameters (temperature, dissolved oxygen, salinity and pH) were monitored daily in tank and monthly in the sea pens. The organic matter was check monthly in sea pens and in tank. The growth performance in terms of body weight gain (BWG) and specific growth rate (SGR) were recorded. Gutted body weight (GBW) and the reproductive performance were evaluated in November 2016 during in season and February 2017 for off season. In terms of BWG, only H. scabra in Ambong gained weight ((63.49 ± 9.49%) while the rest were losing weight. The SGR of H. scabra in Ambong was 0.37 ± 0.04% d-1, while SGR of H. scabra in Kudat and in tank were not stated as no increment of growth H. scabra occurred. The best growth performance was recorded in Ambong as H. scabra in Ambong showed the highest GBW (175.73 ± 4.83 g). Meanwhile, culturing H. scabra in tank was not preferable as the growth performance declined. In terms of reproductive performance, Ambong (1.5868 ± 1.0649%) has the highest GI during the in season, while Kudat (0.6512 ± 0.4233%) has the highest GI during the off season. Variation of GI may be resulted of changing in environmental surrounding and maturity of the gonad itself. As reproductive pattern is a crucial information for aquaculture industry, it is recommended to understand the factor that may regulate the reproduction of H. scabra in Sabah either in wild, sea pen or tank.